Antimicrobial Stewardship in Daily Practice: Managing an Important Resource - Nicole Le Saux; Canadian Paediatric Society, Infectious Diseases and Immunization Committee (Canadian Journal of Infectious Diseases and Medical Microbiology)
Antimicrobial stewardship is a recent concept that embodies the practical, judicious use of antimicrobials to decrease adverse outcomes from antimicrobials while optimizing the treatment of bacterial infections to reduce the emergence of resistant pathogens. The objectives of the present statement are to illustrate the principles of antimicrobial stewardship and to offer practical examples of how to make antimicrobial stewardship part of everyday hospital and outpatient practice. Vital components of antimicrobial stewardship include appropriate testing to diagnose whether infections are viral or bacterial, and using clinical follow-up rather than antibiotics in cases in which the child is not very ill and uncertainty exists. Other specific, important actions include questioning whether positive urine cultures are contaminated when there is no evidence of pyuria or inflammatory changes, and obtaining a chest radiograph to support a diagnosis of bacterial pneumonia. Optimizing the choice and dosage of antimicrobials also reduces the probability of clinical failures and subsequent courses of antimicrobials. A list of common clinical scenarios to promote stewardship is included.